ENDODONTIC MANAGEMENT OF IRREVERSIBLE PULPITIS IN MANDIBULAR SECOND MOLAR: CASE REPORT - Rahaju, Asih; Insani Rohadi, Fikri (Fakultas Kedokteran Gigi Unjani, 2025)
Irreversible pulpitis is a permanent inflammatory condition of the dental pulp, generally caused by bacterial invasion from deep caries, and is characterized by spontaneous pain that cannot be reversed even after the removal of etiologic factors. Permanent mandibular molars, such as tooth 37, often present complex root canal anatomies, including C-shaped canals, two distal canals, or a middle mesial canal, which may directly affect the success of endodontic treatment. This case report aims to describe the management of multiple root canal treatments in a permanent mandibular molar diagnosed with irreversible pulpitis due to deep caries, and to evaluate clinical and radiographic outcomes after therapy. A 35-year-old male patient presented to the Dental Hospital of Jenderal Achmad Yani University with a chief complaint of spontaneous pain in tooth 37 that interfered with daily activities. Clinical examination revealed extensive coronal destruction, a positive painful response to pulp vitality testing, and radiographic findings of deep caries approximating the pulp with periodontal ligament widening but without signs of abscess. A diagnosis of irreversible pulpitis was established, and root canal therapy was performed, including rewalling restoration, biomechanical preparation with hand K-files up to master apical file #25, irrigation with 2.5% sodium hypochlorite and saline, followed by obturation using the lateral condensation technique with resin-based sealer. Final restoration was achieved with an indirect composite to restore masticatory function and prevent reinfection. At follow-up, the patient reported no symptoms, with normal clinical and radiographic findings, indicating successful treatment and functional tooth preservation. In conclusion, irreversible pulpitis in mandibular molars with complex canal morphology can be effectively managed with conventional root canal therapy, where accurate preparation and proper coronal restoration play a more significant role in long-term success than the obturation technique employed. DOI : 10.54052/jhds.v5n2.p227-236